Batasan Aurat Perempuan Dalam Tafsir Al-Hidayah Karya Sa’ad Abdul Wahid: Antara Independensi Hermeneutis atau Reproduksi Wacana Institusional - Rita Zunarti; Shinta Lestari Oktarini; An-Najmi Fikri; Darul Kutni (Contemporary Quran, 2026)
This research is motivated by the discourse and dialectical tension regarding the claim of independence of ijtihad in modern tafsir literature when faced with the sociological reality of exegetes who have strong ties to the authority of religious institutions. The main focus of this study is Tafsir Al-Hidayah by Sa'ad Abdul Wahid, an intellectual figure who once held a central position in the Muhammadiyah Tarjih Council. This tafsir work methodologically claims to use an izdiwajiy approach (a combination of narration and reason) independently, especially in interpreting legal verses such as the limits of women's genitals in Q.S. An-Nuur [24]: 31. Therefore, this study aims to critically examine the claim of independence by tracing and revealing the intertextual relationship between Tafsir Al-Hidayah and the official decisions of institutions contained in the Risalah Adabul Mar'ah Fil Islam. Using library-based qualitative research with Julia Kristeva's intertextuality analysis, this study dissects the ideological relationship between the genotext (the Adabul Mar'ah) and the phenotext (the Tafsir Al-Hidayah). The results of the study show three main findings: first, there is a parallelism of diction and identical argument structure related to the concepts of "modesty" and "social needs"; second, the operation of the politics of citing evidence through strict selection and exclusion of narrations that require the veil in order to accommodate the organization's views; and third, the transposition of functional-sociological logic regarding the public role of women from organizational documents into the narrative of the interpretation. These findings prove that methodological independence in the Tafsir Al-Hidayah is not inauthentic independence because the hermeneutic process has been framed by the collective institutional reasoning of Muhammadiyah.